Septic feline due to pyothorax and associated complications: diagnostic and therapeutic challenge. (Veterinary Science, 2024)
The case of a 2-year-old common European feline was admitted to the emergency room due to weakness, inactivity, and total anorexia of several days of evolution according to on-call veterinarians. Using emergency pleuropulmonary ultrasonography Veterinary Point of care ultrasound, pleural effusion with suspended particles is observed. Thoracentesis was performed, obtaining a fluid with characteristics of empyema, thoracic drains were placed for evacuation and pleural lavages. Upon admission, the patient presented severe myocardial contractile dysfunction with global dilation of the heart. In addition, there were signs of stasis or spontaneous ultrasound contrast, which correlates with prothrombotic events. Bacteriological cure was achieved with pharmacological management and drainage with daily washings after one month of treatment. Improvement is observed in cardiac function (with serial ultrasound monitoring) and thromboprophylaxis without evidence of alterations generated by thrombotic phenomena. Six months after the event occurred, the patient leads a normal life without requiring any support therapy.
Keywords: Pyothorax; Sepsis; Cardiomyopathy dysfunction due to sepsis; Thromboprophylaxis; Pulmonary hypertension; Pleuropulmonary ultrasound